Electrochemical Sensor for Determination of Ascorbic Acid Using a 2-Chlorobenzoyl Ferrocene/Carbon Nanotube Paste Electrode - Sayed Zia Mohammadi; Hadi Beitollahi; Najmeh Nikpour; Rahman Hosseinzadeh (Analytical and Bioanalytical Chemistry Research, 2016)
A chemically modified carbon paste electrode with 2-chlorobenzoyl ferrocene (2CBF) and carbon nanotube (2CBFCNPE) was employed to study the electrocatalytic oxidation of ascorbic acid in aqueous solution using cyclic voltammetry, square wave voltammetry and chronoamperometry. The diffusion coefficient (D = 1.42 × 10-6 cm2 s-1), and the kinetic parameter such as the catalytic rate constant (k = 3.7 × 10 3 M-1 s-1) of ascorbic acid oxidation at the surface of 2CBFCNPE were determined using electrochemical approaches. It has been found that under an optimum condition (pH 4.0), the oxidation of ascorbic acid at the surface of such an electrode occurs at a potential about 85 mV less positive than that of an unmodified carbon paste electrode. Applying square wave voltammetry, in phosphate buffer solution (PBS) of pH 4.0, the oxidation current increases linearly with two concentration intervals of ascorbic acid, one is 1.0 × 10-7-2.5 × 10-6 M and the other is 2.5 × 10-6-7.0 × 10-5 M. Detection limit (3δ) was obtained 64.0 nM. This method was also examined for determination of ascorbic acid in some real samples.